Real-World Experience With a Large Bore Vascular Closure Device During TAVI Procedure: Features and Predictors of Access-Site Vascular Complications - Masiero, Giulia; D'Angelo, Livio; Fovino, Luca Nai; Fabris, Tommaso; Cardaioli, Francesco; Rodinò, Giulio; Benedetti, Alice; Boiago, Mauro; Continisio, Saverio; Montonati, Carolina; Sciarretta, Tommaso; Zuccarelli, Vittorio; et al. (Frontiers in Cardiovascular Medicine, 2022)
Backgrounds Among vascular closure devices (VCDs), the novel collagen plug-based MANTA VCD is the first designed for large bore percutaneous access. We aimed to assess the features and predictors of access-site vascular complications in an unselected trans-femoral transcatheter aortic valve replacement (TF-TAVR) population. Methods Patients undergoing large bore arteriotomy closure with 18F MANTA VCD following TF-TAVR at a large tertiary care center from September 2019 to January 2021 were prospectively analyzed. Primary Outcome was the MANTA VCD access-site-related complications according to Valve Academic Research Consortium-3 (VARC) definitions. Its incidence and predictors were evaluated. Results Eighty-eight patients (median age 82 years, 48% male, 3.3 median Society of Thoracic Surgeons score) undergoing TF-TAVR were included, mostly (63%) treated with a self-expandable device and with outer diameter sizes varied from 18F to 24-F. MANTA VCD technical success rate was 98%, while 10 patients (11%) experienced MANTA VCD access-site vascular complications which included 8% of minor complications and only to 2% of major events resulting in VARC type ≥2 bleeding. Vessel occlusion/stenosis (60%), perforation (20%), and pseudoaneurysm/dissection/hematoma (20%) occurred, but all were managed without surgical treatment. Independent predictors of failure were age (p = 0.04), minimum common femoral artery diameter (CFA) (p < 0.01), sheath-to-femoral-artery ratio (SFAR) (p < 0.01), and a lower puncture height (p = 0.03). A CFA diameter <7.1 mm with a SFAR threshold of 1.01 were associated with VCD failure. Conclusions In a more comers TF-TAVR population, MANTA VCD was associated with reassuring rates of technical success and major access-site vascular complications. Avoiding lower vessel size and less puncture site distance to CFA bifurcation might further improve outcomes.